Load shedding in islanded microgrid using fuzzy linear programming - Maroko, Josiah Teyah; Murage, David K.; Hinga, Peterson Kinyua (Institute of Advanced Engineering and Science, 2024)
The primary goal of any power microgrid is to provide consumers with reliable power. This becomes a challenge with the continued growth of population which necessitates a corresponding rise in power supply. However, this continued rise in power consumption with a limited power supply can result in voltage collapse and ultimately power outage. In times of severe disturbances in an islanded microgrid (IMG), load-shedding (LS) helps to avert the occurrence of a blackout. The IMG is usually supplied by distributed generations (DGs) which have low inertia or inertia less. Thus, when in islanded mode power imbalance is usually solved by performing optimal LS to prevent the system from plunging into a total blackout. This paper presents a hybrid method which is a combination of fuzzy and linear programming algorithm for optimal LS in IMG. The developed method is centered on power generation, load demand and power prioritization. The fuzzy linear programming (FLP) algorithm is tested on the IEEE 14 bus system. The simulation results show that the proposed algorithm is effective in shedding optimal loads to ensure equilibrium is restored and frequency is within set values of 50 Hz.